Theoretical bases and environmental problems of regulation of the rivers rusel, channels and water-economic construction in coastal zones of the South of Russia - S. O. Kurbanov; A. A. Sozayev (Юг России: экология, развитие)
In clause the review of a modern status of the regulated rivers and coastal zones in the south of Russia is made. The analysis of environmental problems of the river pools connected to economic activities of the person and a coastal infrastructure is given. Effective ways of regulation русел and criteria on increase of biopositivity and reliability protectively-regulated constructions are offered.